Exome sequencing shows a novel de novo mutation in ATL1. Issue 1 (January 2014) - Koh, Kishin; Ishiura, Hiroyuki; Miwa, Michiaki; Doi, Koichiro; Yoshimura, Jun; Mitsui, Jun; Goto, Jun; Morishita, Shinichi; Tsuji, Shoji; Takiyama, Yoshihisa
Abstract Background and Aim We experienced treating a male patient born to healthy parents, who presented with spastic gait from childhood, and his son and daughter similarly presented with spastic gait, raising the possibility of a de novo mutation in the patient. With the hypothesis of a de novo mutation in the patient, we carried out exome sequencing of the patient and his parents to identify the gene with a disease‐causative mutation in the patient. Methods The genomic DNA obtained from the patient and his parents were subjected to exome sequencing. We applied various filters to identify candidate de novo mutations. Results We identified three de novo mutations, namely, PLB1 c.3601T>A p.C1201S, PHF2 c.2678C>T p.S893L and ATL1 c.1259A>C p.Q420P. Two of these mutations (ATL1 and PHF2) cosegregated with the disease phenotype in this family. Because the clinical presentations of the affected individuals in this family are typical for spastic paraplegia type 3A, the novel mutation (p.Q420P) in ATL1 is likely the cause of early‐onset spastic paraplegia in this family. Conclusion In the present, study we confirm the efficacy and usefulness of exome sequencing of parent–child trios for establishing the molecular diagnosis of patients with neurological diseases, in whom de novo mutations are suspected.